Streptococcus pneumoniae R6x induced p38 MAPK JNK-mediated Caspase-dependent apoptosis in human endothelial cells - N’Guessan, Philippe Dje; Schmeck, Bernd; Ayim, Abena; Hocke, Andreas C.; Brell, Bernhard; Hammerschmidt, Sven; Rosseau, Simone; Suttorp, Norbert; Hippenstiel, Stefan (Thrombosis and Haemostasis, 2005)
Streptococcus pneumoniae is the major pathogen of communipnetyacquired umonia and a common cause of otitis, meningitis and sepsis. During pneumococci infection accompanied with bacterial invasion and hematogenous spreading, the endothelium is directly targeted by pneumococci and their virulence factors. Therefore, we tested the hypothesis that pneumococci induced endothelial apoptosis. Unencapsulated R6x pneumococci strongly induced apoptosis of human endothelial cells both from lung microvasculature and umbilical vein, whereas an encapsulated strain D39 mainly led to necrotic cell death. Deletion of the gene coding for pneumolysin reduced pneumococci-induced apoptosis in HUVEC. Furthermore, N-acetyl-L-cysteine, an antioxidant thiol, significantly reduced apoptosis caused by R6x, and LDH release induced by D39, pointing to a role for reactive oxygen species in the pathogenesis. Apoptotic cells showed increased cleavage and activity of caspases 6 and 9 but only late activation of caspase 3. Programmed cell death could be strongly reduced by pan-caspase inhibitor zVAD. Reduced levels of Bcl2 and cytosolic increase of apoptosis-inducing factor in pneumococci-infected cells implicated involvement of mitochondrial death pathways. Caspase activation and apoptosis were abolished by cAMP elevation. Moreover, p38 mitogen-activated protein kinase and c-Jun NH2-terminal kinase were activated in pneumococci-infected cells and inhibitors of both kinases strongly reduced pneumococci-induced caspase activation and apoptosis. Hence,kinase- and caspase-dependence of pneumococci-induced endothelial apoptosis may bear relevance to novel therapeutic approaches to pneumococci-related disease.
Keywords: Endothelium; pneumococci; apoptosis; MAP kinase; caspase